Tata Kelola Pengelolaan Badan Usaha Milik Desa (BUMDes) Di Desa Nanga Kiungkang Kecamatan Nanga Taman Kabupaten Sekadau - Kristianus Nova; Ida Rochmawati; Erdi Erdi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This research aims to describe and analyze the governance of the Village-Owned Enterprise (BUMDes) Surya Sarana Mandiri in Nanga Kiungkang Village, Nanga Taman District, Sekadau Regency. The research focus is directed at the application of Good Corporate Governance (GCG) principles, which include Transparency, Accountability, Responsibility, Independence, and Fairness.This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation.The results show that the management of BUMDes Surya Sarana Mandiri has not fully met the principles of good governance. Transparency in budget management is still low, marked by minimal information provided to the community. The Accountability of the management is not yet optimal, evidenced by the absence of structured financial reports and the lack of a tangible contribution to the Village's Original Income (PAD). Responsibility in business management is also not yet effective because the business units have not developed according to local potential. However, the Independence of BUMDes Surya Sarana Mandiri has been able to maintain its institutional autonomy in carrying out economic functions at the village level. There is no pressure or intervention from the village government, community leaders, or other interest groups. Furthermore, regarding the aspect of Fairness, BUMDes Surya Sarana Mandiri has implemented the principle of participation in practice.The research recommends the need for an increase in the BUMDes management's managerial capacity, the strengthening of regulations and supervision, and the active involvement of the community in decision-making. Consistent implementation of GCG principles is believed to be able to enhance the performance of BUMDes and promote sustainable village economic development.